Molecular Evidence for Transstadial Transmission of Ehrlichia canis by Rhipicephalus sanguineus sensu lato Under Field Conditions - Ipek, Neval Duygu Sayin; Ozubek, Sezayi; Aktas, Munir (Oxford Univ Press Inc, 2018)
This study investigated possible transstadial transmission of Ehrlichia canis by Rhipicephalus sanguineus sensu lato collected from shelter dogs and the shelter grounds in Diyarbakir Province of south-eastern Turkey. Totally 225 engorged nymphs were collected from eight infected dogs with E. canis and incubated at 28 degrees C for moulting. Unfed ticks from the shelter grounds comprising 1,800 larvae, 3,100 nymphs, and 85 adults were sorted according to sampling origin, life stage, and sex into 116 pools and screened by 16S rRNA PCR. Nine out of 26 pools of unfed adult ticks were positive for E. canis, with overall infection rate maximum likelihood estimation (MLE) of 4.83 (CI 2.39-8.87). E. canis was detected in three of 12 male pools (MLE 3.22, CI 0.86-8.83) and six of 14 female pools (MLE 6.16, CI 2.59-12.90). No adult pools collected from the shelter grounds were positive. Among 62 unfed nymph pools collected from the shelter, six were infected with E. canis (MLE 0.20, CI 0.08-0.42). No E. canis DNA was detected in any of the larva pools. Our results revealed molecular evidence for transstadial transmission of E. canis by R. sanguineus s.l. both from larva to nymph and from nymph to adult. We found no evidence of transovarial transmission.
Keywords: Ehrlichia canis; Rhipicephalus sanguineus sensu lato; dog; transstadial transmission by R. sanguineus s.l.